Enhancing Students' Innovation and Entrepreneurial Intention Through Digital Marketing Education: A Systematic Literature Review - Husnah, Eni Mabarofiatul; Mubarokah, Rovia Titin; Wati, Andy Prasetyo; Murwani, F. Danardana; Wardana, Ludi Vishnu (PT FORMOSA CENDEKIA GLOBAL, 2024)
The systematic literature review (SLR) article about innovation and entrepreneurial intentions of students through digital marketing education aims to determine the competencies emphasized for students in digital marketing education to increase innovation and entrepreneurial intentions. Competencies are very important for students to face businesses that are switching from conventional to digital. Apart from that, students can run businesses amidst increasingly innovative changes in digital technology. The systematic literature review (SLR) article writing method is a library research method sourced from the Scopus, ProQuest, and Springer Link databases. Articles that are relevant to the research will be analyzed using the prism method. The results of the analysis found that digital marketing education needs to teach students to create new markets, low costs, high profitability, and wide market reach. These competencies can encourage students to increase innovation and entrepreneurial intentions since school.